CONSERVATION CADRE DEVELOPMENT CAMPAIGN AT MIFTAHUL HUDA ISLAMIC JUNIOR HIGH SCHOOL: KAMPANYE PEMBENTUKAN KADER KONSERVASI DI MADRASAH TSANAWIYAH MIFTAHUL HUDA - Chotimah, Husnul; Suharjo, Manis; Tegar, Muhammad; Pitriah, Yuli; Hotimah, Khusnul; Suhartini, Suhartini (Darmabakti Cendekia: Journal of Community Service and Engagements, 2025)
Background: Keraya Village is a coastal area with significant ecotourism potential and mangrove forest resources, yet public awareness—especially among students—of environmental conservation remains low. Objective: This community service program aimed to establish conservation cadres at Madrasah Tsanawiyah (MTs) Miftahul Huda by enhancing students’ knowledge, awareness, and practical skills in environmental preservation. Method: The program employed several stages, including observation, socialization, basic leadership training, cadre inauguration, and the weekly implementation of the Environmental Care (PLH) extracurricular program. The activity involved school administrators, village officials, local community members, and the Indonesian Orangutan Foundation (YAYORIN) as a conservation partner. Evaluation was conducted through observation of student participation and assessment of increased environmental awareness. Results: The results demonstrated the successful establishment of the Greenact Mifda Keraya PLH organization, which actively promotes conservation initiatives within the school and surrounding areas. Furthermore, students’ knowledge increased by an average of 46.0% based on pre-test and post-test results, indicating the program’s effectiveness in strengthening students’ understanding and commitment to environmental conservation. The program also significantly enhanced students’ ecological awareness, leadership abilities, and collaboration between the school and conservation partners. Conclusion: Overall, the program successfully achieved its objective of developing conservation cadres at MTs Miftahul Huda, fostering a generation of environmentally responsible students capable of leading conservation initiatives in their community.